The Development of Mobile Application for Online Psychotherapy and Mood Tracking - ong, pei rui; Darman, Rozanawati (Applied Information Technology And Computer Science, 2023)
The mobile application is developed to solves the problems faced by the public of the ways of handling mental issues, which are that the geographic separation between the therapists and the patients makes psychotherapy difficult to be carried out, the lack of awareness of mental health issues, and the mental illness stigma. This project is to develop a mobile application which served as a tool for mood tracking and as a platform for users to conduct psychotherapy online. The project is developed using prototyping method. The mobile application is constructed using Android Studio and Firebase database. Testing will be conducted at the end of this project to ensure the developed mobile application achieves the objectives. The outcomes of the project are that users can easily connect with professionals in mental health therapy and users can track and always aware of their mental health condition.